Transportation-induced carbon emissions jeopardize healthcare logistics sustainability: Toward a healthier today and a better tomorrow - Khalid Zaman; Muhammad Khalid Anser; Usama Awan; Wiwik Handayani; Hailan Salamun; Abdul Rashid Abdul Aziz; Mohd Khata Jabor; Kamalularifin Subari (Logistics, 2022)
Background: Logistics operations are considered essential for transporting commodities from one location to another, helping to promote global economic activity. On the other hand, its negative impact eclipses its positive impact, namely the rise in healthcare expenditures due to its ecological footprint. Globally, rising out-of-pocket health expenses result from logistic-induced carbon emissions, posing a danger to the long-term viability of healthcare. Methods: Based on this critical fact, this study examined the impact of logistics operations on healthcare costs by controlling for carbon emissions, fuel imports, and economic development across a large cross-section of 131 nations by using the Robust Least Squares Regression. Results: The findings demonstrate a U-shaped association between logistical operations and healthcare expenditures, i.e., if there is a 1% increase in logistics operations, healthcare expenditures decrease by - 2.421% initially, while at later stages, healthcare costs would increase by 0.139%. On the other hand, increased fuel imports and economic growth due to logistics activities are increasing healthcare expenditures with an elasticity estimate of 0.087% and 0.147%, respectively. According to the forecasting predictions, logistics-induced carbon emissions, fuel imports, and economic expansion will increase healthcare expenses. Conclusions: A sustainable logistics operation is critical for strengthening healthcare infrastructure and meeting the global carbon neutrality goal.
Keywords: 650; logistics performance; health expenditures; carbon emissions; fuel imports; economicgrowth